Sweet tea and cigarettes: a taste of refugee life in Jordan - Khoury, R (Refugee Studies Centre, University of Oxford, 2015)
Among refugees in Jordan, utter boredom – the result of restrictions on mobility, prohibitions on employment, and feelings of marginalisation – is an unmistakable source of anguish.